APPLICATION OF DISCOVERY LEARNING TO INCREASE ACTIVITY AND STUDENT LEARNING RESULTS IN UNDERSTANDING THE LIFE ENVIRONMENT IN SMP NEGERI 2 SUKODONO: Bejo Apriyanto, Elan Artono Nurdin, Fahrudi Ahwan Ikhsan, Fahmi Arif Kurnianto - Bejo Apriyanto; Elan Artono Nurdin; Fahrudi Ahwan Ikhsan; Fahmi Arif Kurnianto (Department of Geography Education, University of Jember, 2017)
Abstract The purpose of this study is to analyze the main problem in the classroom and improve student learning outcomes in environmental material in SMP Negeri 2 Sukodono. This research is a classroom action research carried out in 2 action cycles. In this study the data obtained in the form of student learning activities, the value of the discussion, and the value of student learning outcomes. The results showed that with the implementation of discovery learning could be improved the activities and learning outcomes of the students in understanding the environmental problems material. Its indicated by the increase of student learning activities from 65.07% (enough) in the first cycle increased to 76.67 % (good) in cycle II. key words : Discovery Learning, Learning Activity, Learning Outcomes. References Budiningsih, Asri. 2005. Belajar dan Pembelajaran. Jakarta: Rineka Cipta. Dimyati dan Mudjiono. 2006. Belajar dan Pembelajaran. Jakarta: PT. Rineka. Cipta. Hamalik, Oemar. 2008. Kurikulum dan Pembelajaran. Jakarta: Sinar Grafika. Hosnan, M. 2014. Pendekatan Saintifik dan Kontekstual dalam Pembelajaran Abad 21: Ghalia Indonesia Kurniasih, Imas & Sani, Berlin. 2014. Implementasi Kurikulum 2013 Konsep & Penerapan. Surabaya: Kata Pena Mulyasa. 2008. Menjadi Guru Profesional Menciptakan Pembelajaran Kreatif dan Menyenangkan. Bandung : PT. Remaja Rosdakarya. Roestiyah .2001. Strategi Belajar Mengajar. Jakarta: Rineka Cipta. Sudjana, Nana. 2009. Penilaian Hasil Proses Belajar Mengajar. Bandung: PT. Remaja Rosdakarya. Copyright (c) 2017 Geosfera Indonesia Journal and Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License